2020
DOI: 10.1136/bmjopen-2018-025141
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial to investigate the effectiveness of local oestrogen treatment in postmenopausal women undergoing pelvic organ prolapse surgery (LOTUS): a pilot study to assess feasibility of a large multicentre trial

Abstract: ObjectiveTo evaluate the feasibility of a multicentre randomised controlled trial (RCT) comparing oestrogen treatment with no oestrogen supplementation in women undergoing pelvic organ prolapse (POP) surgery.Design and settingA randomised, parallel, open, external pilot trial involving six UK urogynaecology centres (July 2015–August 2016).ParticipantsPostmenopausal women with POP opting for surgery, unless involving mesh or for recurrent POP in same compartment.InterventionWomen were randomised (1:1) to preope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Moreover, recently, Verghese et al 28 . performed a pilot study to assess the feasibility of a multicentre RCT comparing estrogen versus no treatment in women undergoing POP surgery and reported good compliance within the study cohort.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, recently, Verghese et al 28 . performed a pilot study to assess the feasibility of a multicentre RCT comparing estrogen versus no treatment in women undergoing POP surgery and reported good compliance within the study cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that prolapse-specific complaints were not ameliorated by local estrogen treatment, as neither prolapse nor other domain scores (bladder, bowel, sexual function or global pelvic floor score) differed between the intervention and the placebo group. Moreover, recently, Verghese et al 28 performed a pilot study to assess the feasibility of a multicentre RCT comparing estrogen versus no treatment in women undergoing POP surgery and reported good compliance within the study cohort. The authors would like to corroborate this hypothesis as the compliance rate within our study population was also satisfactorily high (176 patients were assessed for eligibility and 120 were randomised, with a retention rate of 86%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When studies had several groups using the same drug with different route of administration, dose, or treatment duration, these groups were merged in the meta-analysis 40,42,50 . In three studies, the control was no intervention 34,51,53 . All other studies used matching placebos.…”
Section: Resultsmentioning
confidence: 99%
“…In symptomatic or recently postmenopausal women, estrogen therapy had no effect to small benefit on sexual function composite score with moderate heterogeneity (SMD, 0.17; 95% CI, 0.01 to 0.32; I 2 = 63%; 2,447 participants, 13 studies 32,36,39,41,42,50,51,53,[57][58][59][60][61][62][71][72][73] ; Fig. 2).…”
Section: Estrogen Therapy Versus Controlmentioning
confidence: 99%